A differentiation program induced by bone morphogenetic proteins 4 and 7 in endodermal epithelial cells provides the molecular basis for efficient nutrient transport by the chicken yolk sac. Issue 2 (12th November 2019) - Bauer, Raimund; Tondl, Philipp; Schneider, Wolfgang J.
Abstract: Background: The mammalian yolk sac provides nutrients for the growing fetus during critical early developmental processes such as neural tube closure, which precedes the functional maturation of the placenta. In contrast, oviparous species such as the chicken rely solely on the yolk sac for transfer of nutrients from the yolk to the developing embryo. However, the molecular mechanisms that provide the yolk sac with nutrient transfer competence remain poorly understood. Results: We demonstrate that the chicken endodermal epithelial cells (EEC), which are in close contact with the yolk, gain their nutrient‐transport competence by a paracrine crosstalk with the blood‐vessel forming mesodermal cell layer. Bone morphogenetic proteins (BMP) 4 and 7 produced by ectodermal and mesodermal cell layers likely initiate a differentiation program of EECs during the transition from the area vitellina to the area vasculosa. BMPs, by inducing SMAD signaling, promote the up‐regulation of endocytic receptor expression and thereby provide the EECs with the molecular machinery to produce triglyceride‐rich lipoprotein particles. Conclusion: This paracrine signaling cascade may constitute the basis for the EEC‐mediated mechanism underlying the efficient uptake, degradation, resynthesis, and transfer of yolk‐derived nutrients into the embryonic circulation, which assures proper energy supply and development of the growing fetus. Key Findings: Endodermal epithelial cells gain their nutrient transport competence during the transition from the area vitellina to the area vasculosa. BMPs signal from the ecto/mesodermal cell sheet to the underlying endoderm, thereby initiating endoderm specification. BMPs thereby provide the endoderm with nutrient transport competence which allows proper nutrition of the growing embryo.